Correction: Liang et al. Integration of Biofloc and Ozone Nanobubbles for Enhanced Pathogen Control in Prenursery of Pacific White Shrimp (Penaeus vannamei). Fishes 2025, 10, 218 - Qinlang Liang; Yazhi Luan; Zhengwen Wang; Jiangbo Niu; Yasong Li; Hua Tang; Zengting Li; Songming Zhu; Gang Liu (Fishes, 2026)
Songming Zhu was not included as an author in the original publication [...]